Spatial orientation – a stable marker for vascular cognitive impairment? - Ellen Lowry; Gillian Coughlan; Sol Morrissey; Stephen Jeffs; Michael Hornberger (Cerebral Circulation - Cognition and Behavior, 2023)
Vascular cognitive impairment (VCI) is the second most prevalent form of dementia, but little is known about the early cognitive and neuroimaging markers. Spatial navigation deficits are an emerging marker for Alzheimer's disease (AD), yet less is known about spatial orientation deficits sensitive to VCI. This case report follows up on the first VCI patient identified to have an egocentric orientation deficit. The study aimed to examine the patient's spatial deficits three years on and gain insights from the addition of the patient's MRI brain scan. A battery of spatial navigation tasks were administered following neuropsychological assessment. Results continue to show spatial orientation deficits. Critically, these changes appear stable and are sensitive to novel spatial tests. Whereas conventional screening tools demonstrate patient recovery. MRI DTI analysis indicates a non-significant trend towards loss of structural integrity to the posterior tracts of the longitudinal superior fasciculus (SLF), while the medial temporal lobe, typically implicated in spatial navigation, is unaffected. This finding potentially reflects reduced network connectivity in posterior to anterior white matter tracts co-existing with spatial orientation deficits. Findings have clinical utility and show spatial orientation as a potential sensitive cognitive marker for VCI.